Subgingivally delivered coenzyme Q10 in the treatment of chronic periodontitis among smokers: A randomized, controlled clinical study - Chetan P. Raut; Kunal S. Sethi; Bhagyashree Kohale; Alefiya Mamajiwala; Ayushya Warang (Elsevier, 2019)
Background: Coenzyme Q10 is an antioxidant whose efficacy in periodontal diseases is well known. However studies regarding its efficacy in smokers with periodontitis are few. Coenzyme Q10 serves as an endogenous antioxidant and its increased concentration in the diseased gingiva effectively suppresses advanced periodontal inflammation. Objectives: The aim of this study is to evaluate the efficacy of coenzyme Q10 as an adjunct to scaling and root planing in smokers with chronic periodontitis. Methods: Total of 40 patients were enrolled for the study. The subjects were divided into control (Scaling and root planing only) and test group (Coenzyme Q10 plus Scaling and root planing). Clinical parameters such as plaque index, modified sulcular bleeding index, probing pocket depth and clinical attachment level. These were assessed at baseline, at 1 month and 3 month. The results were subjected to appropriate statistical analysis. Results: There was a significant improvement in all clinical parameters in the test sites seen at the end of the 1 month and 3 month period. Conclusions: Coenzyme Q10 can be said to have a beneficial effect on smokers with periodontitis when used as an adjunct to scaling and root planing.